2007
DOI: 10.1016/j.pec.2006.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of telephone versus print tailoring for mammography adherence

Abstract: Objective-The purpose of this intervention was to increase mammography adherence in women who had not had a mammogram in the last 15 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 27 publications
0
65
1
Order By: Relevance
“…Empirical intervention studies have demonstrated that barriers can be lowered or modified once they are identified, and can serve as a basis for an intervention plan [35,36]. The present instrument may further serve as a tool for planning and implementing interventions to increase screening attendance among Arab-Israeli women.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical intervention studies have demonstrated that barriers can be lowered or modified once they are identified, and can serve as a basis for an intervention plan [35,36]. The present instrument may further serve as a tool for planning and implementing interventions to increase screening attendance among Arab-Israeli women.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 These models have been applied in studies of tailored interventions to alter women's behaviors toward having a mammogram every 2 years. Tailored interventions usually use scripted texts, adjusted to each woman's stage of contemplation [9][10][11] and her barriers against undergoing the examinations. [11][12][13] Several randomized large-scale studies found that telephone interventions to lower individual barriers to screenings increased mammography use more than did usual care or active control.…”
Section: Tailored Telephone Interventionmentioning
confidence: 99%
“…Many studies have claimed an additive effect of adding printed material to phone messaging (Champion et al, 2007;Rimer et al, 2001;Rimer et al, 2002). Lants et al reported that mailed reminder letters from a physician combined with telephone contact from a health educator significantly increased the odds of participants receiving breast and cervical cancer screening (Lantz et al, 1995).…”
Section: Discussionmentioning
confidence: 99%